Rehabilitation of Executive Functions: Systematic Review of Technological Stimulation Devices - Ramos-Galarza, Carlos (2023)
Executive functions are high-level mental abilities that are located in the frontal lobe and allow humans to regulate their behavior. These cognitive skills are initiative, working memory, problem solving ability, inhibition, monitoring, verification, planning, among others. In the processes of stimulation or rehabilitation of executive functions, we work with material based on pencil and paper, therefore, it is essential to generate technological proposals that can help in the processes of rehabilitation of executive functions. In this context, we present a research that conducted a quantitative systematic review of technological devices used for neuropsychological stimulation and rehabilitation of executive functions. The research concludes by analyzing the contribution of having technological resources to rehabilitate executive functions and the need for future research to develop new technological tools in the neuropsychological rehabilitation process.